Nostalgic Collective Memory, Populist Rhetoric Exposure, and Social Transformation in Peri-Urban Communities of Palembang, South Sumatra, Indonesia: A Cross-Sectional Analytical Study - Firzan Dahlan; Grace Freya Purba (Open Access Indonesia Journal of Social Sciences, 2026)
Nostalgic collective memory and exposure to populist rhetoric have emerged as significant sociocultural forces shaping contemporary social transformation in peri-urban areas of Southeast Asia. This cross-sectional analytical study examined the associations between nostalgic collective memory orientation, populist rhetoric exposure, and positive social transformation outcomes among 384 peri-urban residents in three purposively selected peri-urban sub-districts in a major city in South Sumatra, Indonesia. Participants were recruited through proportional stratified random sampling from sub-districts characterized by rapid urbanization and socioeconomic heterogeneity. They completed structured questionnaires assessing nostalgia levels (adapted 12-item scale, Cronbach alpha=0.82), populist rhetoric exposure (10-item scale), collective memory strength (8-item scale, alpha=0.78), community engagement, political trust, and perception of social transformation across six measured dimensions. Overall, 201 respondents (52.3%) perceived positive social transformation. Bivariate analysis demonstrated that high nostalgia levels were associated with 2.14-fold increased odds of perceiving positive social transformation (95% CI: 1.42-3.23; p=0.001), while high exposure to populist rhetoric was associated with 2.05-fold increased odds (95% CI: 1.36-3.09; p=0.001). Active community engagement was associated with 1.84-fold increased odds (95% CI: 1.22-2.77; p=0.004), and strong collective memory orientation was associated with 1.65-fold increased odds (95% CI: 1.10-2.48; p=0.016). Multiple logistic regression identified nostalgia level (AOR=1.89; 95% CI: 1.22-2.93; p=0.004), populist rhetoric exposure (AOR=1.76; 95% CI: 1.13-2.74; p=0.012), and community engagement (AOR=1.62; 95% CI: 1.05-2.50; p=0.029) as independent predictors. The model demonstrated moderate discriminative ability (AUC=0.735; Nagelkerke R²=0.187). These findings illuminate complex mechanisms through which nostalgic orientation, populist messaging, and community cohesion influence perceptions of social change in peri-urban Southeast Asian contexts.